Luther vs. Pope Leo : a conversation in purgatory - Hinlicky, Paul R. (Abingdon Press, 2017)
"The seeds for a new Reformation. Martin Luther and Pope Leo X awake in heaven. It is the year 2017 and they have been asleep since the posting of the 95 Thesis in 1517. Naturally, they are disoriented upon waking. To their mutual chagrin not only does each discover the other face to face in heaven, but they learn that by divine decree they are roomed together indefinitely. The Pope's first reaction to the news is to gather that this is his purgatory for the sins of the Medicis. Luther despairs that he is in hell: 'It was works after all,' he surmises. This book tells a story, that is to say, it is the author's imaginary reconciliation in heaven between Martin Luther and Pope Leo X who work through the issues that divided them in their historical encounter. As such this book turns Luther and Leo into the instruments of a commitment to Protestant-Catholic ecumenical reconciliation as signaled by the Joint Declaration on Justification by the Vatican and the Lutheran World Federation in 1999 and subsequently subscribed by The United Methodist Church. Yet this fantasy--a genre chosen for its teaching potential and popular appeal--is a well-grounded one as will be annotated in the endnotes and explained in the Afterword. In the notes and Afterword the basis in history for all the assertions put on the lips of Luther and Leo in the text will be documented and the theology by which their heavenly reconciliation is fantasized will be argued"--